The mediaeval roof structure over the nave of the cathedral in Kamień Pomorski in the light of architectural and dendrochronological research - Schaaf, Ulrich; Prarat, Maciej; Ważny, Tomasz (Średniowieczna więźba dachowa nad nawą środkową katedry w Kamieniu Pomorskim w świetle badań architektoniczno-dendrochronologicznych, 2022)
The subject of the article is the roof structure over the central nave of the cathedral in Kamień Pomorski. Although there are numerous studies relating to the history of the construction of this cathedral or to the development of historic roof structures in general, none of them has yet included the roof structures discussed in this work. This situation and the need to repair the construction have justified the carrying out of the architectural research to learn its construction history and carpentry technique. The research on the existing material substance in the eastern trusses, taking into account the following aspects: load-bearing structure, sides of timber framing, carpentry joints, a system of carpentry assembly marks, building material, and its processing. The results of these analyses were supplemented and compared with the results of dendrochronological research and that presented in the literature on the subject. As a result of this research, it has been possible to establish that the chancel of the Kamień Pomorski cathedral is crowned with a cross-braced collar beam roof structure, which dates back to the early 1360s. It was strengthened in the late 1860s by additional entablature above the vault rise, and an inclined queen post structure and a king post structure. The next strengthening took place fragmentarily as part of the repair that has been underway since the end of the late 2010s. Despite its age and repairs, the original structure has survived to a great extent. The type of the roof structure used above the nave in Kamień Pomorski – a cross-braced collar beam roof structure – served a specific construction function in the Middle Ages – the construction of a roof over a vault within the boundaries of the roof. A preliminary literature review has shown that examples of such solutions have survived in various parts of Europe to the present day, but only in a small number. In the territory of Poland, so far it is the only known example of this kind from the 14th century. Currently, the remaining cross-braced collar beam roof structures over both arms of the transept and chancel of the cathedral in Kamień Pomorski are included in the architectural research. A wider study on this type of mediaeval roof structures, and attempts to compare the roof structures of the Kamień Pomorski cathedral against a broader background are desirable in the future.
Architectus : Pismo Wydziału Architektury Politechniki Wrocławskiej, 2022, nr 4 (72), s. 3-15
Keywords: architektura; Kamień Pomorski; cathedral; roof structure; Middle Ages; architectural research; dendrochronological research; katedra; więźba dachowa; średniowiecze; badania architektoniczne; badania dendrochronologiczne